Excess liquidity in the euro area: Sources and remedies - Marek Dąbrowski (Center for Social and Economic Research (CASE), 2023)
The excess liquidity in the euro area is a product of a long period of quantitative easing. It changed the operational framework of the European Central Bank (ECB)'s monetary policy from the scarce reserves system (SRS) to the abundant reserves system (ARS). To eliminate excess liquidity and return to the SRS, the ECB must intensify quantitative tightening, which is also essential for successful disinflation. Fiscal adjustment can help in this process and mitigate the risk of financial instability. This document was provided by the Economic Governance and EMU Scrutiny Unit at the request of the Committee on Economic and Monetary Affairs (ECON) ahead of the Monetary Dialogue with the ECB President on 25 September 2023.
Keywords: E41; E51; E52; E58; 330; iquidity; monetary policy; base money; central bank assets; central bank liabilities; scarce reserve system; abundant reserve system; quantitative easing; quantitative tightening; euro area; European Central Bank; US Federal Reserve System